Pengembangan kompetensi editorial dan tata kelola jurnal ilmiah berbasis DOAJ melalui program pelatihan di STIKES Vincentius A Paulo Surabaya - Ni Nyoman Wahyu Lestarina; Nora Ekawati; Veronica Silalahi; Gabriel Wanda Sinawang; Selly Omega Dila Teju (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2026)
The management of high-quality scientific journals continues to face numerous challenges. This community service activity aimed to evaluate the effectiveness of a training program designed to improve participants’ understanding of DOAJ standards and national journal accreditation. This community service activity employed a pre-experimental one-group pretest–posttest design. In the initial phase, 16 participants took a pretest to assess their baseline knowledge; subsequently, they participated in a training session comprising material delivery and interactive discussions. After the activity concluded, a posttest was administered to measure the participants’ improved understanding. Data analysis to test the significance of differences before and after the training used the Wilcoxon test. Descriptive analysis results indicated an increase in the average score from 112.5 to 146.3 on the final knowledge test. Based on the Wilcoxon Signed-Rank Test, a Z-value of -3.237 was obtained (p = 0.001, p < 0.05), indicating that training on scientific journal management in accordance with DOAJ standards and national accreditation standards significantly improved participants’ understanding. Furthermore, the effect size indicated by the matched-rank biserial correlation of -0.950 suggests that the training’s impact falls into the very large category. The training not only enhanced participants’ knowledge of open access principles, policy transparency, and editorial governance but also standardized their understanding, resulting in a more consistent level of understanding among participants.